PERANAN ELECTRONIC WORD OF MOUTH DAN FEAR OF MISSING OUT DALAM MEMBENTUK PURCHASE INTENTION PRODUK MIXUE DI SURABAYA - Stanislaus Steven Bambang Kusumo; Yonathan Palumian; Nony Kezia Marchyta; Wilma Laura Sahetapy (CV. Denasya Smart Publisher, 2025)
This study examines the influence of Electronic Word of Mouth (eWOM) on purchase intention among Mixue consumers, considering the Fear of missing out (FOMO) factor. Employing a quantitative approach, the research surveyed 108 ice cream enthusiasts in Surabaya, Indonesia. Data collection was conducted through an online questionnaire using the Google Form platform. The data analysis utilized the Partial Least Square (PLS) method with SmartPLS 4.0 software to evaluate the relationships between eWOM, FOMO, and purchase intention variables. The findings indicate a positive and significant relationship between eWOM and purchase intention. Furthermore, FOMO is proven to play a mediating role in the relationship between eWOM and purchase intention. These results have important implications for digital marketing strategies, particularly in the food and beverage industry. The study highlights the importance of leveraging eWOM and FOMO mechanisms in marketing campaigns as effective strategies to drive consumer purchasing decisions. This research contributes to a deeper understanding of consumer behavior in the digital era, specifically within the Indonesian market context.